Image Compression Using Imaging Tomography Technique - AbdulJabar, Hameed (Iraqi Journal of Science, 2024)
Imaging Tomography is very powerful tool as a nondestructive imaging method,it use forward and back projection technique to create an image for a slice of anobject. This technique had been simulated in this research on images as acompression method. The result shows that imaging Tomography technique has highcompression ratio for large images and it has forward relationship with the imagedimensions. The Fourier Slice Theorem filter used to retrieve the images from its 2-D projection, image quality was acceptable (5-7 dB) comparing with compressionratio that achieved, using another filter it could give better result.